New Regulations for Foods Offered to School Children in Chile: Barriers to Implementation - Prochownik Katherine; Vera Vergara Mariana; J.Cheskin Lawrence (International Journal of Nutrition, 2015)
Objective: To prevent childhood obesity, the Chilean government has recently implemented food regulation laws that apply to schools. This paper reviews the literature regarding the challenges in successfully integrating policies to regulate foods offered in schools. In addition, to understand some of the potential implementation barriers, a survey was conducted to evaluate how well food regulation laws were understood and implemented in Chilean schools. Methodology: A narrative literature review was conducted regarding food regulation policies in Chilean schools and potential barriers to implementation. This informed a subsequent descriptive, qualitative survey which was conducted in the Valparaíso region of Chile to examine knowledge, practices, and potential barriers to implementation of the new regulations. Twelve randomly-selected school food kiosk owners completed a survey and structured interview. Visual observations were also performed at each food kiosk. Content analysis identified trends in food items sold and determined the depth of understanding kiosk owners have of a specific new food law,
Keywords: Food regulation